Lithic studies : Anatolia and beyond - Baysal, Adnan, (Archaeopress Archaeology, 2022)
This volume shows networks of cultural interactions by focusing on the latest lithic studies from Turkey, Greece, and the Balkans, bringing to the forefront the connectedness and techno-cultural continuity of knapped and ground stone technologies.